2001
DOI: 10.1021/ac000977m
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Temperature Oscillations on DNA Sequencing by Capillary Electrophoresis

Abstract: Although capillary electrophoresis is a powerful sequencing technology, the low heat capacity of a capillary can make difficult the precise control of its temperature, particularly when the capillary is heated to reduce compressions in the separation of DNA sequencing fragments. In this paper, we demonstrate that minute oscillations in the capillary's temperature result in significant degradation in the number of theoretical plates, the resolution between adjacent peaks, and the number of bases of DNA sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…We do not have a convincing hypothesis to explain these variations at the present time, however one potential cause is the temperature variations in the nonthermostated capillary. Small local changes in temperature may result in buffer viscosity changes, which previously have been shown to affect separations [21].…”
Section: Electropherograms Of Individually Detected Microspheresmentioning
confidence: 98%
“…We do not have a convincing hypothesis to explain these variations at the present time, however one potential cause is the temperature variations in the nonthermostated capillary. Small local changes in temperature may result in buffer viscosity changes, which previously have been shown to affect separations [21].…”
Section: Electropherograms Of Individually Detected Microspheresmentioning
confidence: 98%
“…The Monte Carlo method can be used for modeling the diffusion processes without "explicitly" solving System 5 [22]. This method, however, requires longer calculation times to achieve the same accuracy as the explicit numerical solution of System 5.…”
Section: Numerical Solutionmentioning
confidence: 99%
“…It was observed that a temperature change as small as 0.058C was sufficient to induce an observable mobility shift, due to the change of equilibrium between partially melted and double stranded DNA molecules (unpublished data). In addition, it was observed that minute oscillations as small as l0.18C in a capillary's temperature resulted in significant degradation in the number of theoretical plates due to the laminar flow induced by the periodic thermal expansion and contraction of the separation medium [41]. Therefore, it is crucial that accuracy and precision better than l0.058C be maintained to ensure reproducibility in the CDCE process, if isothermal temperature control is employed.…”
Section: Resultsmentioning
confidence: 99%